Danielle Walker's make it easy : a meal prep and menu planning guide for stress-free cooking - Walker, Danielle (Chef) (Ten Speed Press, 2024)
"A super-flexible meal prep cookbook featuring 125 healthy gluten-free, grain-free, and paleo recipes plus 16 weeks of menu plans, detailed meal prepping advice, grocery lists, and more-from the New York Times bestselling author of the Against All Grain series"--